A Flexible Approach to MySQL Backup Creation – flexmysqlbackup - Todorov, Dimitar (Computer Science and Interdisciplinary Research Journal, 2025)
Creating backups in MySQL is an integral part of database management, particularly crucial in environments with large data volumes and critical information. Data recovery in the event of a system crash, data loss, or migration requirements is made possible by timely and accurate backups. MySQL is one of the most popular databases, utilized by numerous companies and projects. Mysqldump is a standard tool for backup and recovery. While effective for standard backups, mysqldump encounters several challenges in more complex scenarios, particularly when compatibility across different MySQL versions is required. This paper proposes a new approach, flexmysqlbackup, which provides more flexible backup options and rapid recovery without the limitations imposed by MySQL versions. Implementation scripts are presented, along with experiments demonstrating and proving its effectiveness.